Detection of low-energy charged particles by channel electron multipliers. (1st November 2022) - Newson, D.M.; Shipman, M.; Brawley, S.J.; Kadokura, R.; Babij, T.J.; Cooke, D.; Leslie, D.E.; Laricchia, G.
Abstract: Experimental determinations of the detection efficiency for positrons impacting a channel electron multiplier with incident energies between 0–1400 eV are presented. A log-normal dependence with energy is established and used to compute the positron-to-positronium detection efficiency ratio as a function of positronium energy, as required for determining quantities involving the ratio of positron and positronium rates. A log-normal energy-dependence is also observed in results of previous work with electrons, protons and ions.